Evaluation of the Effect of Nebivolol in Bone Defect Healing in An Experimental Rat Model - Qurrat-ul-Ain Haider; Shabana Ali; Muhammad Waqar Aslam Khan; Kulsoom Farhat; Novera Sohail Bajwa; Nausheen Ata (Pakistan Armed Forces Medical Journal, 2023)
Objective: to evaluate the beneficial role of Nebivolol on bone formation in Experimental model of rat.